Transperineal Magnetic Resonance Imaging-targeted Biopsy versus Transperineal Template Prostate Mapping Biopsy in the Detection of Localised Radio-recurrent Prostate Cancer. Issue 9 (September 2016) - Kanthabalan, A.; Abd-Alazeez, M.; Arya, M.; Allen, C.; Freeman, A.; Jameson, C.; Kirkham, A.; Mitra, A.V.; Payne, H.; Punwani, S.; Ramachandran, N.; Walkden, M.; et al.
Abstract: Aims: Multi-parametric magnetic resonance imaging (mpMRI) may identify radio-recurrent intra-prostatic cancer accurately. We aimed to compare visually directed MRI-targeted biopsies (MRI-TB) to an accurate reference standard – transperineal prostate mapping (TPM) biopsies with 5 mm sampling – in the detection of clinically significant cancer in men with biochemical failure after radiotherapy. Materials and methods: A retrospective registry analysis between 2006 and 2014 identified 77 men who had undergone mpMRI followed by MRI-TB and TPM. Clinical significance was set at two definitions of disease. Definition 1 was Gleason ≥ 4+3 and/or maximum cancer core length ≥ 6 mm. Definition 2 was Gleason ≥ 3+4 and/or maximum cancer core length ≥ 4 mm. Results: Of the 77 patients included, the mean age was 70 years (range 61–82; standard deviation 5.03). The median prostate-specific antigen (PSA) at the time of external beam radiotherapy (EBRT) was 14 ng/ml (interquartile range 7.83–32.50). The most frequent EBRT dose given was 74 Gy over 37 fractions. Eight patients had iodine-seed implant brachytherapy or high dose rate brachytherapy. Neoadjuvant/adjuvant hormonal therapy use was reported in 38. The time from EBRT to biochemical recurrence was a median of 60 months (interquartile range 36.75–85.00). The median PSA at the time of mpMRI was 4.68 ng/ml (interquartile range 2.68–7.60). The median time between mpMRI and biopsy was 2.76 months (interquartile range 1.58–4.34). In total, 2392 TPM and 381 MRI-TB cores were taken with 18% and 50% cancer detection, respectively. Detection rates of definition 1 clinically significant cancer were 52/77 (68%) versus 55/77 (71%) for MRI-TB and TPM, respectively. MRI-TB was more efficient requiring 1 core versus 2.8 cores to detect definition 2 cancer. Conclusion: MRI-TB seems to have encouraging detection rates for clinically significant cancer with fewer cores compared with TPM, although TPM had higher detection rates for smaller lower grade lesions. Highlights: Multi-parametric MRI may identify radio-recurrent intra-prostatic cancer accurately. MRI-targeted biopsies (MRI-TB) were compared with transperineal prostate mapping (TPM) biopsies. MRI-TB has encouraging detection rates for significant cancer with fewer cores. TPM had higher detection rates for smaller lower grade lesions.